How religious and spiritual beliefs explain prolonged grief disorder symptoms - Christian, K.; Aoun, Samar; Breen, Lauren (Routledge, 2018)
This study investigated the importance of religious and spiritual beliefs in daily life in explaining prolonged grief disorder (PGD) symptomatology. Participants were 588 bereaved adults who completed a questionnaire. The importance of spiritual beliefs in daily life explained a small to medium, significant 3% of variance in PGD symptoms, but religious beliefs in daily life did not. Individuals who placed moderate importance on spiritual beliefs in their daily life may experience more intense grief.